2021
DOI: 10.3114/fuse.2021.08.14
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring the species Rhizophagus intraradices (formerly Glomus intraradices)

Abstract: The nomenclatural type material of Rhizophagus intraradices (basionym Glomus intraradices) was originally described from a trap pot culture established with root fragments, subcultures of which later became registered in the INVAM culture collection as FL 208. Subcultures of FL 208 (designated as strain ATT 4) and a new strain, independently isolated from the type location (ATT 1102), were established as both pot cultures with soil-like substrate and in vitro root organ culture. Long-term sampling of these cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In this context, to capture all the intraspecific morphological variability, Walker et al . (2021) emphasized the importance of characterizing new species based on analyses of multiple cultures grown long enough and the need for intermittent redescriptions of species in the Glomeromycotina, as type specimens may represent only a subset of the phenotype based on variation in anatomical/histochemical characters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, to capture all the intraspecific morphological variability, Walker et al . (2021) emphasized the importance of characterizing new species based on analyses of multiple cultures grown long enough and the need for intermittent redescriptions of species in the Glomeromycotina, as type specimens may represent only a subset of the phenotype based on variation in anatomical/histochemical characters.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus plausible that biotic and/or abiotic factors induce the production of spores with two divergent morphologies primarily in vivo, but not under the very stable in vitro conditions commonly used for the propagation of the strain DAOM 197198 of R. irregularis. In this context, to capture all the intraspecific morphological variability, Walker et al (2021) emphasized the importance of characterizing new species based on analyses of multiple cultures grown long enough and the need for intermittent redescriptions of species in the Glomeromycotina, as type specimens may represent only a subset of the phenotype based on variation in anatomical/histochemical characters.…”
Section: Confusion In Culture Collections and Incorrect Taxonomic Ass...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widely accepted fact that different AMF genera could affect plant metabolome differently [ 52 ], one of the main observations of the present study is that AMF species belonging to the same genus may induce similar, but not strictly identical, metabolomic responses in A. officinalis plants, without being strongly related phylogenetically. Indeed, the latest updates regarding the phylogenetic classification of under-investigated AMF strains showed that R. irregularis is phylogenetically more closely related to R. clarus than to R. intraradices [ 53 ]. Therefore, the outcome of the association in terms of, e.g., plant growth promotion and metabolites enhancement, is highly specific to the identity of the AMF symbiont [ 2 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, continuous in vitro root production can be achieved, enabling mycorrhizal colonization, without the need for aboveground plant tissues (Bécard & Fortin, 1988; Danesh et al, 2006; Srinivasan et al, 2014). Wan et al (1998) used Ri T‐DNA–transformed Daucus carota roots associated with Glomus intraradices (now Rhizophagus intraradices [Walker et al, 2021]) to show that this system could be used to detect dose responses of reductions in percentage of root colonization following exposure to increasing concentrations of copper sulfate, glyphosate, and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid, with no effects observed for benomyl, chlorothalonil, and dimethoate. Both Zocco et al (2008) and Campagnac et al (2008) examined mycorrhization of D. carota by R. intraradices following exposure to the fungicides fenpropimorph and fenhexamid, with Zocco et al (2008) reporting no effects and Campagnac et al (2008) reporting significant declines driven by fenpropimorph only.…”
Section: Tier 1: Methodological Approachesmentioning
confidence: 99%